Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2014
DOI: 10.1145/2556288.2557290
|View full text |Cite
|
Sign up to set email alerts
|

Captioned photographs in psychosocial aged care

Abstract: In this paper we examine the use of a novel social technology to support the provision of formal aged care services to clients who live in their own homes. Social technologies offer enormous potential for enhancing aged care, but research on their use in aged care has largely focused on institutional or informal care settings, rather than formal care in the home. Meanwhile, technologies for aging in place typically focus on monitoring and security, rather than psychosocial support. We conducted a field study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 24 publications
(18 reference statements)
0
10
0
Order By: Relevance
“…Waycott et al [31] developed a tool to facilitate message and media sharing and conducted a study in which caregivers used the tool to communicate with their elderly clients. Their results showed that photographs with captions were able to increase and enhance communication, and were well-suited to promote psychosocial care.…”
Section: Introductionmentioning
confidence: 99%
“…Waycott et al [31] developed a tool to facilitate message and media sharing and conducted a study in which caregivers used the tool to communicate with their elderly clients. Their results showed that photographs with captions were able to increase and enhance communication, and were well-suited to promote psychosocial care.…”
Section: Introductionmentioning
confidence: 99%
“…At the end of each field study we conducted final interviews with the participants and their care managers to evaluate how well the intervention had worked for them. In addition, we analysed the content that participants created and shared on Enmesh (Waycott et al, 2014;.…”
Section: Methodsmentioning
confidence: 99%
“…The participants enjoyed using Enmesh. It facilitated social engagement, provided new opportunities for creative self-expression, and enhanced the relationship between clients and care managers (Vetere et al, 2012;Waycott et al, 2014;. The project was an evidencebased intervention: it was designed based on the likelihood of success, drawing on a review of the literature on social isolation interventions (Cattan, White, Bond, & Learmouth, 2005), feedback from care managers, and the close involvement of the aged care partner organization.…”
Section: Beneficencementioning
confidence: 99%
See 1 more Smart Citation
“…Studies have explored how families use different mechanisms to share health information, including photos [2,15]. Sharing photos is beneficial to inspire memory collection [11,12], support communication [9,14,16] and social connectedness [1,7], and encourage reciprocity and reminiscence [4,10]. Inspired by this work, we were interested to know whether photo sharing might also be useful for families provision of care, specifically on health.…”
Section: Introductionmentioning
confidence: 99%